2023
DOI: 10.3390/nu15122771
|View full text |Cite
|
Sign up to set email alerts
|

Prebiotic Supplementation during Lactation Affects Microbial Colonization in Postnatal-Growth-Restricted Mice

Abstract: Background: An inadequate perinatal nutritional environment can alter the maturation of the intestinal barrier and promote long-term pathologies such as metabolic syndrome or chronic intestinal diseases. The intestinal microbiota seems to play a determining role in the development of the intestinal barrier. In the present study, we investigated the impact of consuming an early postnatal prebiotic fiber (PF) on growth, intestinal morphology and the microbiota at weaning in postnatal-growth-restricted mice (PNGR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…Among the members of the phylum Firmicutes , the families Lachnospiraceae and Oscillospiraceae were the most abundant bacterial taxa and the major butyrate-producers [3–6]. The abundance of the Oscillospiraceae members was reduced in malnourished mice [7], suggesting that members of the family Oscillospiraceae might be correlated with host nutirition and health.…”
Section: Introductionmentioning
confidence: 99%
“…Among the members of the phylum Firmicutes , the families Lachnospiraceae and Oscillospiraceae were the most abundant bacterial taxa and the major butyrate-producers [3–6]. The abundance of the Oscillospiraceae members was reduced in malnourished mice [7], suggesting that members of the family Oscillospiraceae might be correlated with host nutirition and health.…”
Section: Introductionmentioning
confidence: 99%
“…MCTs represent a promising therapeutic intervention to reduce fungal colonisation without significantly affecting the bacterial composition of the host gastrointestinal tract. Marousez et al [ 24 ] investigated the impact of consuming early postnatal prebiotic fibre (PF) on growth, intestinal morphology, and the microbiota during weaning in postnatal-growth-restricted mice (PNGR). They found that the PNGR mice had a decreased body weight and ileal crypt depth during weaning compared to the control group and microbiota alterations.…”
mentioning
confidence: 99%